Hubungan Motivasi Belajar Terhadap Pemahaman Konsep Matematis Siswa - Ikhlas Anwar Lahagu; Telaumbanua, Yakin Niat; Lase, Sadiana; Mendrofa, Netti Kariani (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
Mathematical concept understanding is an essential ability that students must master in mathematics learning to enable them to comprehend and apply mathematical ideas effectively. However, in reality, many students experience difficulties in understanding mathematical concepts due to low learning motivation, which ultimately affects their learning outcomes. This study aims to examine the relationship between learning motivation and mathematical concept understanding among Grade XII students. This research employed a quantitative approach with a correlational research design. The population consisted of 90 Grade XII students, and the sample was selected using purposive sampling from class XII IPA-1. The research instruments included a learning motivation questionnaire and a mathematical concept understanding test, both of which had been tested for validity and reliability. Data analysis techniques involved normality testing, homogeneity testing, and hypothesis testing using the Product Moment correlation method. The results showed that students’ learning motivation was categorized as high, with a percentage of 78.79%. Meanwhile, students’ mathematical concept understanding was mostly in the good and very good categories, with percentages of 51.52% and 27.27%, respectively. The hypothesis test indicated that the calculated t value (4.354) was greater than the t table value (2.040) at the 5% significance level. The correlation coefficient obtained was r = 0.616, with a coefficient of determination of 37.94%. These findings indicate that learning motivation is not the sole factor influencing students’ mathematical concept understanding; other internal and external factors also contribute.